2020
DOI: 10.3390/pr8060736
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Different Ageing Technologies of Wine Spirit by Application of Near-Infrared (NIR) Spectroscopy and Volatile Quantification

Abstract: The traditional ageing of wine spirits is done in wooden barrels, however, high costs have led to the search for alternative technologies, such as the use of stainless steel tanks with wooden staves and the application of micro-oxygenation. This work evaluates the changes in the major volatile compounds of wine spirits aged for 6, 12 and 18 months in wooden barrels and stainless steel tanks with micro-oxygenation. For both ageing technologies, two types of wood (Limousin oak and Portuguese chestnut wood) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Near infrared (NIR) spectroscopy has been applied for the evaluation of the quality of many foods and beverages given its simplicity, fast analysis, and the fact that it can be non-destructive. The NIR technique has been successfully used in different foods and beverages [ 11 , 12 , 13 ] to measure different parameters of pear and apple quality attributes and nutraceutical properties [ 14 , 15 , 16 ]. NIR technology has been mostly used to measure the total soluble solids of a variety of fruits [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared (NIR) spectroscopy has been applied for the evaluation of the quality of many foods and beverages given its simplicity, fast analysis, and the fact that it can be non-destructive. The NIR technique has been successfully used in different foods and beverages [ 11 , 12 , 13 ] to measure different parameters of pear and apple quality attributes and nutraceutical properties [ 14 , 15 , 16 ]. NIR technology has been mostly used to measure the total soluble solids of a variety of fruits [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The developed database models achieved 100% recognition rate for 374 wines from three different countries (Australia, Chile, and China). Zaukuu and coworkers combined NIR spectroscopy and e-tongue technology for the determination of adulterants in high quality Tokaj wines [134]. Partial least square regression modeling gave a coefficient of determination (R 2 ) value of 0.98 and 0.97 for the e-tongue and NIRS, respectively.…”
Section: Alcoholic Drinks (Wines Beers Spirit)mentioning
confidence: 99%
“…By coupling NIR spectroscopy with two-dimensional correlation spectroscopy, they proved that this technique can dramatically improve quality evaluation efficiency over NIR alone [135]. Another group, Anjos et al [134], found that NIR spectroscopy can discriminate aging practices of wine spirits (barrel wood species in which it was aged, aging time, etc.) with up to 90% accuracy.…”
Section: Alcoholic Drinks (Wines Beers Spirit)mentioning
confidence: 99%
See 1 more Smart Citation
“…New technologies or methods should be developed to meet the increasing requirements for rapid and nondestructive determination. Several advanced optical technologies have been studied and reported in meat quality evaluation with satisfying results, such as computer vision [14,15] , near-infrared (NIR) spectroscopy [16][17][18] and Raman spectroscopy [19][20][21] .…”
Section: Introduction mentioning
confidence: 99%